Use of ultrasonography as an auxiliary predictive method in the reproductive evaluation of bulls - Silva, Brenda Pereira da; Fernandes, Caroline Baena; Fernandes, Giovanna de Freitas; Carvalho , Grasiella Gomes Machado; Christino, Kelen do Carmo; Chagas, Walker Nunes; Pina, Eliene Porto Sad; Leite , Dala Kezen Vieira Hardman (Seven Editora, 2024)
Brazil is the leader in beef exports, being one of the largest producers in the world, in addition to occupying the third position of the world’s largest milk producer. To obtain such status, it is necessary to make a large investment in the area of animal production, especially with regard to genetics, nutrition and health. The genetic improvement of breeding stock is one of the most important and necessary factors, because it directly contributes to the efficiency of production and reproduction of animals. Currently, the selection of animals aiming at sexual precocity is considered one of the strategies with a direct impact on the profitability of cattle farming. Methodologies for the analysis of reproductive characteristics have always been renewed, and among them, ultrasonography was considered a safe, non-invasive technique that allows monitoring the morphology and functionality through the echogenicity presented, without causing any risk to the integrity of the bull’s reproductive system. This technique can be used as an indicator of sexual precocity, since pubertal animals appear to have a more hyperechoic testicular parenchyma when compared to prepubertal animals of the same age, and this fact can be explained by the changes that occur in the testicular parenchyma due to the onset of puberty and spermatogenesis. The use of ultrasonography is of paramount importance as a complementary diagnostic method in the andrological examination, as it facilitates the choice with greater precision and precocity of bulls that are already suitable for reproduction. DOI:https://doi.org/10.56238/sevened2024.007-042